2009
DOI: 10.2466/pr0.104.3.879-895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Youth Fit for Life Protocol on Physiological, Psychological, and Behavioral Factors at YMCA Calgary After-School Care Sites

Abstract: Youth inactivity and inappropriately high weight is a problem in the United States, Canada, and much of the industrialized world. Physiological and behavioral changes associated with the Youth Fit For Life protocol, a physical activity and nutrition education treatment based on self-efficacy theory, were assessed in 7- to 12-yr.-olds (N - 43) from Calgary, Alberta, Canada. Body Mass Index, strength, and cardiorespiratory endurance significantly improved over a 12-wk. period when contrasted with changes based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Research suggested that there was considerable correspondence between runs of 12, 9, 6, and 3 min in the elementary school age group [41]. Pilot testing for children of ages 5 to 8 years indicated that the correlation of a previously used run/walk tests of 6 min [29,30], and a 3-min version, was strong at 0.70, p<0.001. Thus, the 3-min version was used in this study because of its greater acceptability to the younger participants and easier administration in the limited spaces available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggested that there was considerable correspondence between runs of 12, 9, 6, and 3 min in the elementary school age group [41]. Pilot testing for children of ages 5 to 8 years indicated that the correlation of a previously used run/walk tests of 6 min [29,30], and a 3-min version, was strong at 0.70, p<0.001. Thus, the 3-min version was used in this study because of its greater acceptability to the younger participants and easier administration in the limited spaces available.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis of 16 studies on the effects of the Youth Fit For Life treatment suggested its favorable effects on body composition that were lesser in ages 5 through 8 years (ES=0.10) than in ages 9 through 12 (ES=0.16) [27]. Additional research evaluated its effects on outputs of moderate-to-vigorous physical activity (ES=0.33) [28], fruit and vegetable intake (ES Mean =0.21) [29,30], strength (ES Mean =0.62) [29,30], cardiovascular, and endurance (ES Mean =0.17) [29,30] and, in ages 7 years and above, physical selfconcept (ES Mean =0.26) [29][30][31][32][33][34], mood (ES Mean =0.31) [30,31,[34][35][36], self-efficacy (ES Mean =0.19) [29,30,[32][33][34][35], and free-time physical activity (ES Mean =0.42) [29,33,34] changes.…”
mentioning
confidence: 99%
“…A concerted effort to overcome PA barriers can result in mastery of PA (Annesi et al . , Fawcett et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Task self‐efficacy (perceived physical competence), self‐regulatory self‐efficacy (managing perceived barriers) (Annesi et al . )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation